2009
DOI: 10.1021/ic901391y
|View full text |Cite
|
Sign up to set email alerts
|

Reactivities of Fe(IV) Complexes with Oxo, Hydroxo, and Alkylperoxo Ligands: An Experimental and Computational Study

Abstract: In a previous paper (Jensen et al., J. Am. Chem. Soc. 2005, 127, 10512), we reported the synthesis of the turquoise-colored intermediate [Fe IV (β-BPMCN)(OO t Bu)(OH)] 2+ (Tq; BPMCN = N,N′-bis (2-pyridylmethyl)-N,N′-dimethyl-trans-1,2-diaminocyclohexane). The structure of Tq is unprecedented, as it represents the only synthetic example to date of a non-heme Fe IV complex with both alkylperoxo and hydroxide ligands. Given the significance of similar high-valent Fe intermediates in the mechanisms of oxygenase en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 50 publications
3
51
0
Order By: Relevance
“…Indeed, substituted phenols are usually the substrates of choice in order to probe the H-atom abstracting ability of transition-metal complexes. [26,27] Overall, from our initial substrate screening, it seems clear that 1 cannot perform oxygen-atom transfer to alkenes, sulfides or alkanes but it readily activates and oxidizes O À H and N À H bonds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, substituted phenols are usually the substrates of choice in order to probe the H-atom abstracting ability of transition-metal complexes. [26,27] Overall, from our initial substrate screening, it seems clear that 1 cannot perform oxygen-atom transfer to alkenes, sulfides or alkanes but it readily activates and oxidizes O À H and N À H bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Similar KIE values for the oxidation of TTBP have been measured in other metal systems in which a hydrogen-atom abstraction mechanism is postulated. [27,30] Surprisingly, 1 H NMR analysis of the oxidized product from the reaction with TTBP failed to show the characteristic singlet at d = 6.7 ppm expected for tBu PPQ, [31] which suggests the formation of a structurally different oxidized species. By means of 1D and 2D we could determine that, indeed, the oxidized species corresponds to compound 2 tBu (Figure 3), which is a structural isomer of tBu PPQ.…”
mentioning
confidence: 99%
“…Theoretical studies of such biomimetic models may not only identify the key elements that determine their chemical reactivities, but may also provide insight into intermediates and reactivities of parent enzymes (Shaik et al, 2007a; de Visser et al, 2013). To date, DFT calculations have been applied extensively to various types of non-heme iron species (Scheme 1) (Bassan et al, 2002, 2005a,b; Roelfes et al, 2003; Decker and Solomon, 2005; Kumar et al, 2005; Quinonero et al, 2005; Berry et al, 2006; Bernasconi et al, 2007, 2011; de Visser, 2006, 2010; Hirao et al, 2006a, 2008a,b, 2011; Rohde et al, 2006; Decker et al, 2007; de Visser et al, 2007, 2011; Johansson et al, 2007; Noack and Siegbahn, 2007; Sastri et al, 2007; Sicking et al, 2007; Bernasconi and Baerends, 2008, 2013; Comba et al, 2008; Dhuri et al, 2008; Fiedler and Que, 2009; Klinker et al, 2009; Wang et al, 2009a, 2013b; Cho et al, 2010, 2012a, 2013; Geng et al, 2010; Chen et al, 2011; Chung et al, 2011b; Seo et al, 2011; Shaik et al, 2011; Vardhaman et al, 2011; Wong et al, 2011; Ye and Neese, 2011; Gonzalez-Ovalle et al, 2012; Gopakumar et al, 2012; Latifi et al, 2012; Mas-Ballesté et al, 2012; McDonald et al, 2012; Van Heuvelen et al, 2012; Ansari et al, 2013; Kim et al, 2013; Lee et al, 2013; Sahu et al, 2013; Tang et al, 2013; Ye et al, 2013; Hong et al, 2014; Sun et al, 2014). The intriguing reactivity patterns of these complexes are the result of active involvement of electrons in d-type MOs, which gives rise to multi-state scenarios (Shaik et al, 1998; Schröder et al, 2000; Schwarz, 2011).…”
Section: Applications Of Dftmentioning
confidence: 99%
“…[6,7] Interestingly, using the method introduced by Bordwell et al and Mayer, [8] it was found that the hydrogen-abstraction ability of a metal oxo moiety and the related metal hydroxo in those models are very similar. [7,9,10] [12] Using Mn IV (salen) complexes (salen = N,N'-bis(salicylidene)ethylenediamine anion), Fujii and co-workers also found that Mn IV = O demonstrates much faster rate than its protonated Mn 2 )] can be investigated under three different pH conditions. Hydrogen abstraction reactions from 9,10-dihydroanthracene substrate were performed in acetone/ water (4:1) under nitrogen, and the product distributions are summarized in Table 1 3+ at pH 1.5 gives a 3.0 % yield of anthracene and an 8.3 % yield of anthraquinone, a surprisingly similar product distribution to that for the Mn IV =O moiety at pH 13.4.…”
mentioning
confidence: 99%